Sistem Pendukung Keputusan Pemilihan Wisata Kuliner dengan Memanfaatkan AHP dan SAW berbasis Web - Puji Astuti, Norafika; Hartami Santi, Indyah; Kirom, Sabitul (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2025)
Blitar City has strong potential in culinary tourism but lacks a system to guide tourists in selecting destinations that fit their preferences. This study develops a web-based decision support system to provide efficient and objective recommendations. The system offers a simple, responsive interface with automated processing, reducing the need for complex manual input. It applies the Analytical Hierarchy Process (AHP) to assign weights to criteria such as price, location, facilities, and operating hours, and the Simple Additive Weighting (SAW) method to rank alternatives. AHP testing produced consistent weights with a Consistency Ratio (CR) below 0.1, while SAW successfully generated ranked recommendations. The Agile approach was used for development, allowing iterative progress. Black Box Testing confirmed full functionality, while validation through expert and user questionnaires showed feasibility scores of 81.25% and 86.6%. Results show the system is accurate, feasible, and effective in supporting culinary tourism and digital development in Blitar City. Keywords: decision support system, ahp, saw, culinary tourism, web